Pemeliharaan Ikan Lontok (Ophiocara porocephala Valenciennes, 1837) Sebagai Upaya Konservasi Dengan Pemberian Pakan Udang Kecepe (Acetes sp.) - Khairul Khairul; Uswatul Hasan (Biogenesis: Jurnal Ilmiah Biologi, 2018)
The spangled gudgeon (Ophiocara porocephala Valenciennes, 1837) is one of the fish that live in the waters of Belawan and has important economic value to the community. However, lately the wild population continues to decline due to factors that supposedly over fishing, waters pollution and habitat degradation. Cultivation effort is one of the solutions to keep the preserved and decrease arrests in nature. The study of associated cultivation efforts need to be made through research. The purpose of this research is to know the frequency of feeding the shrimp kecepe (Acetes sp.) the right against the growth of absolute spangled gudgeon fish. The benefits of research as the basis for the management and preservation of fish decreased as well as the increasingly Spangled Gudgeon fish efforts do local fish conservation in Belawan Rivers. Results of the study showed the average length of the highest absolute growth was at the treatment D (1.10 cm), followed the treatment C (0.90 cm), treatment B (0.80 cm), and the lowest at the treatment A (0.73 cm). Analysis of variance results indicate that the Fh (8 **) > 0.05 Ft (4.07) means the treatment of natural feeding shrimp kecepe very real influence (highly significant) against the growth of the absolute length of the juvenile spangled gudgeon.